ERP Framework Design for SME: A Solution for an Effective Management for Garments Manufacturing - Perez, Carla Carmela (Southeast Asian Journal of Science and Technology, 2019)
Today’s market climate is one that encourages collaboration. Enterprises often recognize the need to incorporate integrated-enterprise programs in order to do this. At present, ERP systems offers models which are hard to implement in Small and Medium Enterprises (SME) due to some limitations and issues such as mutual synchronization of multi-type resources, limited customization, bulky upgrading cost, solution integration, industry functionality, backup hedge and technology updates. These issues somewhat build the implementation of ERP systems distressing, complex and time consuming and generates the massive change in ERP framework to enhance ERP systems infrastructure and functionality. This research aimed to discuss the positive characteristics associated with ERP systems in SMEs; to design an ERP framework for garment manufacturing industry in favor of SME community; and to design the prototype of the ERP system framework. Human-centered design methodology was used in the research as a main method which comprises 3 phases namely, (1) Inspire; (2) Ideate; (3) Implement. The results discussed that positive outcomes of ERP are reduced data entry errors and cost reduction. Increased operational efficiency can also be observed when properly implemented along with better insights. The proposed framework design initiates different ERP occurrences. It was designed specifically for the X Apparel Enterprise. Thus, implementing ERP system framework design in garments manufacturing industry, getting sustainable garment quality through continuous quality improvement to meet customer quality requirement and high customer satisfaction will certainly be met and/or achieved regardless of constraints.